Immunoblotting and enzyme-linked immunosorbent assay for the diagnosis of pemphigoid gestationis. - Sitaru, C; Powell, J; Messer, G; Bröcker, E; Wojnarowska, F; Zillikens, D (2004)
OBJECTIVES: To investigate the sensitivity of immunoblotting and enzyme-linked immunosorbent assay (ELISA) to detect autoantibodies to bullous pemphigoid antigen 180 in patients with pemphigoid gestationis and to correlate autoantibody serum levels with disease activity. METHODS: In serum samples obtained from 44 pregnant patients before initiation of therapy and from the same number of healthy blood donors, the autoantibody reactivity was assayed by immunofluorescence microscopy on human skin sections as well as Western blot analysis and 2 different ELISAs by using recombinant forms of the immunodominant domain of BP180. In addition, ELISA reactivity with this autoantigen was assayed in 6 patients during the course of the disease, and its correlation with the clinical disease activity was estimated by applying the Spearman rank correlation test. RESULTS: By indirect immunofluorescence microscopy, complement-fixing autoantibodies to the dermal-epidermal junction were found in 93% of patients' sera. By immunoblotting and ELISA, autoantibodies to bullous pemphigoid antigen 180 were detected in 93% and 86.3% of pemphigoid gestationis patients, respectively, but in none of the healthy controls. Serum levels of autoantibodies as detected by ELISA paralleled the patients' disease activity. CONCLUSIONS: Our study shows that immunoblotting and ELISA are sensitive tools for the detection of autoantibodies to bullous pemphigoid antigen 180 in patients with pemphigoid gestationis. In addition, the ELISA is useful to monitor autoantibody serum levels. LEVEL OF EVIDENCE: II-2